Cellulose ionic conductor with tunable Seebeck coefficient for low-grade heat harvesting. (15th September 2022) - Hu, Yang; Chen, Minzhang; Qin, Chaoran; Zhang, Jipeng; Lu, Ang
Abstract: Natural polymer-based thermoelectric materials are significant for sustainable development because they can be used to directly harvest heat into electricity while avoiding the utilization of petroleum-based resources. Herein, cellulose ionic conductors were fabricated by using cellulose as the hydrogel matrix and cellulose solvents as the electrolytes. p -type and n -type thermoelectric generators (TEG) based on cellulose ionic conductor were obtained, with Seebeck coefficient of 2.61 and −1.33 mV/K, due to the different interactions between quaternary ammonium cations and cellulose. The cellulose TEG-based supercapacitor showed a high specific capacitance and the ability of charging with thermal energy and powering electronic devices with a maximum power density of 0.42 mW/m 2 . Moreover, a flexible module-type TE harvester with 10 pairs of p - n legs was assembled for body heat harvesting, delivering a thermovoltage of 0.42 V for a temperature gradient of 13 K, enabling waste/biological heat conversion, temperature monitoring and temperature control. Graphical abstract: Unlabelled Image